Impact of Thin-Ideals in Influencer Posts Promoting Healthy vs. Unhealthy Foods on Tweens’ Healthy Food Choice Behavior - De Jans, Steffi; Hudders, Liselot; Naderer, Brigitte; De Pauw, Valentina (Frontiers in Psychology, 2022)
The current study examines how social media influencers can be deployed to promote healthy food choice behavior among tweens. In particular, we investigate whether tweens’ healthy food choice behavior can be stimulated by using a thin-ideal influencer in a sponsored influencer post promoting unhealthy versus healthy food. A two-by-two, between-subjects experimental study (influencer weight: thin-ideal versus overweight; snack type: unhealthy versus healthy) was conducted with 146 tweens (11 to 13 years old, 73 boys). Results show that tweens’ choice for a healthy snack was higher when a (female) overweight influencer promoted an unhealthy snack (compared to a healthy snack). Using a thin-ideal influencer promoting an unhealthy versus healthy snack did not affect tweens’ healthy food choice. While there were no interaction effects of influencer weight and snack type on source effects (influencer credibility, influencer admiration and trans-parasocial interactions), the results did show that the influencer was perceived as less credible and was admired less when she was overweight versus when she had a thin-ideal body-type.